2010
DOI: 10.1186/1471-2377-10-52
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency lesions adjacent to the dorsal root ganglion alleviate spasticity and pain in children with cerebral palsy: pilot study in 17 patients

Abstract: BackgroundCerebral palsy (CP) may cause severe spasticity, requiring neurosurgical procedures. The most common neurosurgical procedures are continuous infusion of intrathecal baclofen and selective dorsal rhizotomy. Both are invasive and complex procedures. We hypothesized that a percutaneous radiofrequency lesion of the dorsal root ganglion (RF-DRG) could be a simple and safe alternative treatment. We undertook a pilot study to test this hypothesis.MethodsWe performed an RF-DRG procedure in 17 consecutive CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 39 publications
1
25
0
3
Order By: Relevance
“…The dorsal roots are intact in patients with poliomyelitis, and sensory stimulation tests were applied successfully in our case. The locations of the DRG can only be confirmed via the administration of contrast material in pediatric patients . The exact location of the DRGs was confirmed using the sensory stimulations test and the administration of contrast material in the present case (Figure ).…”
Section: Discussionsupporting
confidence: 51%
“…The dorsal roots are intact in patients with poliomyelitis, and sensory stimulation tests were applied successfully in our case. The locations of the DRG can only be confirmed via the administration of contrast material in pediatric patients . The exact location of the DRGs was confirmed using the sensory stimulations test and the administration of contrast material in the present case (Figure ).…”
Section: Discussionsupporting
confidence: 51%
“…Two systematic reviews were included in this category; one reviewed BoNT‐A injections and the other reviewed pharmacological interventions (BoNT‐A and ITB) for children with CP and other life‐limiting conditions . Individual studies in these reviews were included if they met the eligibility criteria . Two studies were excluded as an outcome measure of pain was not reported …”
Section: Resultsmentioning
confidence: 99%
“…Radiofrequency thermocoagulation on DRG has been widely applied for the treatment of various chronic pains. [ 5 , 6 ] The corresponding area of sensory nerve is not able to regenerate after DRG injury, so the therapeutic effects of radiofrequency thermocoagulation are exact and constant. Radiofrequency thermocoagulation has been widely used in the control of pain caused by cancer.…”
Section: Discussionmentioning
confidence: 99%